ANALISIS EVALUASI PBM DI PROIGRAM STUDI TEKNIK MESIN UMSB PASCA MEMPEROLEH AKREDITASI B - Nefli Yusuf; hariadi hariadi (LPPM Universitas Muhammadiyah Sumatera Barat, 2020)
Evaluation Analysis of Teaching and Learning Process forthe Undergraduate Mechanical Engineering Program of West Sumatera Muhammadiyah Unversity in the Post Accreditation of B. This evaluation of TLP (Teaching and Learning Process) is done as a source to analyze the acquireeachievements after the enactment of the 2016 curriculum. The analitical results are expected as input to be able to further quality improvement ofeducation inthe Mechanical Engineeringprogramof West Sumatera Muhammadiyah University. The evaluation was done by giving questions to 17 students of 2017 class and 14 students of2018 class for 32 courses inthe semester of 1, 2, 3 and 4. Questions were made in the statementof 12 sentences, That are foursentences regarding to the material understanding, foursentences regarding to the learning process and foursentences regarding to the teaching process. Number 1 means not-agree, 2 means disagree, 3means quite agree, 4 means agree and 5means strongly agree. If this statement is truly agreed, it means that the TLP process has gone well as expected. Recapitulation of all answering results is obtained an average of 3.92, very close to the number 4 (agree)which may be interpreted thatthe educational process in the Mechanical Engineering programof West Sumatera Muhammadiyah Unversityis satisfiedappropriateto an accreditation obtainedof B. The answering variations of statements regardingmaterial understanding should probably become special attention to be reviewed. Keywords : evaluation, achievement, teaching and learning process, qulity, review